تأثير إضافة مستخلص الزنجبيل والعكبر (البروبوليس) في بعض المؤشرات الإنتاجية عند دجاج اللحم( الفروج) - عبد العزيز, فهيم; دلا, توقيق; العلي, رامي (Latakia University Journal -Biological Sciences Series, 2019)
بهدف تحسين النمو، وزيادة الوزن الحي، ومردود ذبائح الدواجن ، استخدم مستخلص الزنجبيل والعكبر(البروبوليس) في تغذية فروج اللحم؛ وذلك بإضافته إلى الخلطات العلفية ، بصورة بودرة جافة . تمت تجربة البحث على الهجين التجاري لدجاج اللحم الهبرد Hubberd المتوفر في السوق المحلية؛ فقسمت طيور التجربة إلى أربع مجموعات (مجموعة طيور الشاهد، وثلاث مجموعات طيور التجربة)، أضيف إلى غذائها مسحوق الزنجبيل بمعدل(1, 2 , 3 ) كغ/ طن علف مع البروبوليس بمعدل (150 , 250 , 500 ) غ/ طن علف . دلت النتائج على وجود فروق معنوية بين طيور التجربة التي تغذت على المخاليط بالنسب (0002+250 ، 3000+500 ) غ/ طن علف، مع طيور الشاهد، وطيور التجربة التي تغذت على المخلوط بالنسبة (1000+ 150) غ/ طن علف عند مستوى ثقة (P% 0.05≤ )، وذلك بالنسبة إلى صفات: الوزن الحي، وكمية العلف المستهلكة، ومعامل التحويل الغذائي، ونسبة التصافي، ومتوسط وزن الذبيحة ، وقد راوحت الأوزان الحية بين (2220)، و(2522) غ ، وبلغ معامل التحويل الغذائي (951.، و2.1). على حين كانت نسبة التصافي (65.9%) عند الشاهد، و(65.8-68.9%) عند طيور التجربة ، كما دلت الدراسة على عدم وجود فروق معنوية بين طيور التجربة، عند استخدام الزنجبيل والبروبوليس بالنسبة (2000+250 ) غ/ طن علف، والنسبة(3000+500 )غ/ طن علف، وكذلك لم يلاحظ أيضاً وجود فروق معنوية بين طيور الشاهد، وطيور التجربة عند استخدام النسبة (1000+ 150) غ/ طن علف عند مستوى ثقة (P≤ % 0.05 )، وذلك بالنسبة إلى الصفات المذكورة، وأشارت الدراسة الاقتصادية إلى زيادة المردود، والكفاءة الاقتصادية باستخدام هذه المستخلصات بنسبة بلغت نحو (18%) . Aiming to develop the growth, to increase the living body weight and the rate of carcasses yield in poultry, ginger and propolis extract were used in feeding broiler chicken by adding it in the form of dry powder. The research was carried out on Hubberdhybrid which are locally existed. Birds were divided into four groups (control group and three experiment groups). Ginger and propolis extract, the ginger rate was added to experiment birds food (1, 2, 3)Kg / ton feed and the propolis rate was (150,250,500) g / ton feed . The results referred to difference between control and experiment birds which fed on ginger and propolis extract at the rate (2000+250 ، 3000+500 ) g / ton feed with comparison of control birds and experiment birds which fed on ginger and propolis extract at the rat (1000+150 )g / ton feed at ( p≤ 0.05 % ) of the living body weight , the feed conversion ratio , dressing percentage and carcass weight , the live weight was about (2220,2522) g . The feed conversion ratio reached (1.95, 2.1 %), the dressing percentage of control birds was (65.9 %) while the dressing percentage of experiment birds was between (65.8 - 68.9%). The study showed that there is no difference between ginger and propolis extract at the rate (2000+250) g / ton feed with rate (3000+500 ) g / ton feed at ( p≤ 0.05 % ) and also there is no difference between ginger and propolis extract at rate (1000+150) g / ton feed and control birds at (p≤ 0.05 %) of former characters .The economic study assured to increase the production andeconomic efficiency from using ginger and propolis extract in the diet at the rate was ( 18%).